2016
DOI: 10.1088/1748-0221/11/02/c02065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the energy-separation filter on the performance of each detector layer in the sandwich detector for single-shot dual-energy imaging

Abstract: A: A novel sandwich-style single-shot detector has been built by stacking two indirectconversion flat-panel detectors for preclinical dual-energy mouse imaging. Although this single-shot method is more immune to motion artifacts compared with the conventional dual-shot method (i.e., fast kVp switching), it may suffer from reduced image quality because of poor spectral separation between the two detectors. Spectral separation can be improved by using an intermediate filter between the two detector layers. Adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Therefore, quantum noise in DE images in this work is most sensitive to the quantum noise arising from the high-energy projection [18]. Kim et al [19] experimentally showed the trade-offs between contrast and quantum noise in the single-shot DE images. All the results that are shown below are obtained using a sandwich detector without an intermediate filter.…”
Section: Working Principle Of the Sandwich Detectormentioning
confidence: 83%
“…Therefore, quantum noise in DE images in this work is most sensitive to the quantum noise arising from the high-energy projection [18]. Kim et al [19] experimentally showed the trade-offs between contrast and quantum noise in the single-shot DE images. All the results that are shown below are obtained using a sandwich detector without an intermediate filter.…”
Section: Working Principle Of the Sandwich Detectormentioning
confidence: 83%
“…Therefore, there would exist an optimal material (e.g. atomic number and composition) and thickness for an intermediate filter [13], but those optimal figures will be dependent upon detector materials/thickness as well as application-specific tasks (including energies). Theoretical cascadedmodel analysis approach may be helpful for a better design of sandwich detector [10,14,15].…”
Section: Jinst 14 C01021mentioning
confidence: 99%
“…The only difference between two detector layers is thickness of phosphor layers: ∼ 34 mg cm −2 and ∼ 67 mg cm −2 for the front and rear detectors, respectively. The MTF, NPS, and DQE of each detector layer of the sandwich detector have recently been measured for various applied tube voltages (50 − 90 kVp) and thicknesses of an intermediate copper (Cu) filter (t IF = 0 − 0.5 mm) [6]. Those measured data are used in this study.…”
Section: Measurementsmentioning
confidence: 99%
“…The energy separation can be further controlled by placing a filter layer between the two detector layers, and in this case filter material and its thickness are additional variables for determining the extent of energy separation. Unfortunately, it is hard to obtain high contrast DE images from a sandwich detector without sacrificing image noise because a large energy separation (i.e., low transmittance) reduces the number of x-ray photons reaching the rear detector, increasing image quantum noise [3,5,6]. Subtractive DE reconstruction further increases DE image noise [4].…”
Section: Introductionmentioning
confidence: 99%